Smart instruction and learning: Collaborative digital Libraries - Edzan, N.N.; Abdullah, I.I. (2000)
The Smart School is one of the seven flagship applications of the Malaysian Multimedia Super Corridor. Its driving force is technology and this technology will be the enabling infrastructure for new teaching-learning processes. In line with the emergence of the Smart School concept, this paper will propose a model for a collaborative digital library to be used by Malaysian secondary schools. The proposed model will incorporate the five basic features of a digital library. It will allow collaborators (eg. partner schools, organisations, associations and individuals) to cooperatively develop electronic sources and upload them to a hosting system. However, various issues have to looked into before the model can be fully implemented and integrated within the Malaysian secondary school system.